THE PRACTICALLITY OF RIGID BODY DYNAMICS CONSTRUCTIVIST MODULE AS PHYISC LEARNING RESOURCE OF SENIOR HIGH SCHOOL STUDENTS - Nurdawia Nurdawia; Zulirfan Zulirfan; Fakhruddin Z (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
This study aims to measure the practicality of physics constructivist modules in the dynamics of rotation and rigid body balance using ADDIE’s model. The module practicality stages are: preparation, research introduction, practicality testing, filling out questionnaires, analyzing and conclusions, revising, and practical. There are 25 students and one physics teacher who asked using a questionnaire with 5 practical indicators, namely: efficiency, presentation of module material, ease of use, conformity with science, and implementation of constructive elements. The results of module practicality testing data analysis showed that the module efficiency level was 65.83 with the practical category, the module presentation rate was 90.16 with a very practical category, the module's ease of use was 86.08 with a very practical category, the degree of conformity with the science was 95,0 with a very practical category, and the level of implementation of constructive elements is 88.8 with a very practical category. Overall, the practicality of constructivist physics learning modules is 85.17 with a very practical category. Based on the results, it can be concluded that the constructivist physics learning module of rotational dynamics and rigid body balance is declared practical to be used as a source of learning for high school physics students.